MDR1-P-glycoprotein behaves as an oncofetal protein that promotes cell survival in gastric cancer cells - Rocco, Alba; Compare, Debora; Liguori, Eleonora; Cianflone, Alessandra; Pirozzi, Giuseppe; Tirino, Virginia; Bertoni, Alessandra; Santoriello, Margherita; Garbi, Corrado; D'Armiento, Maria; Staibano, Stefania; Nardone, Gerardo (Laboratory investigation, 2012)
P-glycoprotein (P-gp), traditionally linked to cancer poor prognosis and multidrug resistance, is undetectable in normal gastric mucosa and overexpressed in gastric cancer (GC). We propose that P-gp may be involved in Helicobacter pylori (Hp)-related gastric carcinogenesis by inhibiting apoptosis. Aim of the study was to evaluate the expression of P-gp in fetal stomach and in Hp-related gastric carcinogenesis, the epigenetic control of the multi-drug resistance-1 (MDR1) gene, the localization and interaction between P-gp and Bcl-xL and the effect of the selective silencing of P-gp on cell survival. P-gp and Bcl-xl expression was evaluated by immunohistochemistry on 28 spontaneously abortive human fetuses, 66 Hp-negative subjects, 138 Hp-positive chronic gastritis (CG) of whom 28 with intestinal metaplasia (IM) and 45 intestinal type GCs. P-gp/Bcl-xL colocalization was investigated by confocal immunofluorescence microscopy and protein–protein interaction by co-immunoprecipitation, in basal conditions and after stress-induced apoptosis, in GC cell lines AGS and MKN-28 and hepatocellular carcinoma cell line Hep-G2. The role of P-gp in controlling apoptosis was evaluated by knocking down its expression with a specific small interfering RNAs in stressed AGS and MKN-28 cell lines. P-gp is expressed in the gastric mucosa of all human fetuses while, it is undetectable in adult normal mucosa and re-expressed in 30/110 Hp-positive non-IM-CG, 28/28 IM-CG and 40/45 GCs. P-gp expression directly correlates with that of Bcl-xL and with the promoter hypomethylation of the MDR1 gene. In GC cell lines, P-gp is localized on the plasma membrane and mitochondria where it colocalizes with Bcl-xL. Co-immunoprecipitation confirms the physical interaction between P-gp and Bcl-xL in AGS, MKN-28 and Hep-G2, at both basal level and after stress-induced apoptosis. The selective silencing of P-gp sensitizes GC cells to stress-induced apoptosis. P-gp behaves as an oncofetal protein that, by cross-talking with Bcl-xL, acts as an anti-apoptotic agent in Hp-related gastric carcinogenesis.